Parvalbumin and GABA Microcircuits in the Mouse Superior Colliculus - Villalobos, Claudio A.; Wu, Qiong; Lee, Psyche H.; May, Paul J.; Basso, Michele A. (Frontiers in Neural Circuits, 2018)
The mammalian superior colliculus (SC) is a sensorimotor midbrain structure responsible for orienting behaviors. Although many SC features are known, details of its intrinsic microcircuits are lacking. We used transgenic mice expressing reporter genes in parvalbumin-positive (PV+) and gamma aminobutyric acid-positive (GABA+) neurons to test the hypothesis that PV+ neurons co-localize GABA and form inhibitory circuits within the SC. We found more PV+ neurons in the superficial compared to the intermediate SC, although a larger percentage of PV+ neurons co-expressed GABA in the latter. Unlike PV+ neurons, PV+/GABA+ neurons showed predominantly rapidly inactivating spiking patterns. Optogenetic activation of PV+ neurons revealed direct and feedforward GABAergic inhibitory synaptic responses, as well as excitatory glutamatergic synapses. We propose that PV+ neurons in the SC may be specialized for different circuit functions with the SC rather than forming a homogeneous, GABAergic neuronal subtype as they appear to in other regions of the brain.